Relación de algunas plantas y hongos mexicanos raros, amenazados o en peligro de extinción y sugerencias para su conservación - Vovides, Andrew P.; Luna, Victor; Medina, Guadalupe (Instituto de Ecología, A.C., 1997)
A revised list of some rare, threatened and endangered plant species of Mexico is presented. Listing is by IUCN category, vegetation type and state. A list of threatened fungi is included for the first time. The role of the botanic gardens in the conservation of these species is discussed. A numerical analysis of the reported species by family, IUCN category and vegetation is also presented.